Clinical, Immunological, and Molecular Profile of Chronic Granulomatous Disease: A Multi-Centric Study of 236 Patients From India - Rawat, Amit; Vignesh, Pandiarajan; Sudhakar, Murugan; Sharma, Madhubala; Suri, Deepti; Jindal, Ankur; Gupta, Anju; Shandilya, Jitendra Kumar; Loganathan, Sathish Kumar; Kaur, Gurjit; Chawla, Sanchi; Patra, Pratap Kumar; et al. (Frontiers in Immunology, 2021)
Background Chronic granulomatous disease (CGD) is an inherited defect in phagocytic respiratory burst that results in severe and life-threatening infections in affected children. Single center studies from India have shown that proportion of autosomal recessive (AR) CGD is more than that reported from the West. Further, affected patients have high mortality rates due to late referrals and difficulties in accessing appropriate treatment. However, there is lack of multicentric collaborative data on CGD from India. Objective To describe infection patterns, immunological, and molecular features of CGD from multiple centers in India. Methods A detailed proforma that included clinical and laboratory details was prepared and sent to multiple centers in India that are involved in the care and management of patients with inborn errors of immunity. Twelve centers have provided data which were later pooled together and analyzed. Results Of the 236 patients analyzed in our study, X-linked and AR-CGD was seen in 77 and 97, respectively. Male female ratio was 172:64. Median age at onset of symptoms and diagnosis was 8 and 24 months, respectively. Common infections documented include pneumonia (71.6%), lymphadenitis (31.6%), skin and subcutaneous abscess (23.7%), blood-stream infection (13.6%), osteomyelitis (8.6%), liver abscess (7.2%), lung abscess (2.9%), meningoencephalitis (2.5%), splenic abscess (1.7%), and brain abscess (0.9%). Forty-four patients (18.6%) had evidence of mycobacterial infection. Results of molecular assay were available for 141 patients (59.7%)—CYBB (44.7%) gene defect was most common, followed by NCF1 (31.9%), NCF2 (14.9%), and CYBA (8.5%). While CYBA variants were documented only in Southern and Western parts of India, a common dinucleotide deletion in NCF2 (c.835_836delAC) was noted only in North Indian population. Of the 174 patients with available outcome data, 67 (38.5%) had expired. Hematopoietic stem cell transplantation was carried out in 23 patients, and 12 are doing well on follow-up. Conclusions In India, proportion of patients with AR-CGD is higher as compared to Western cohorts, though regional differences in types of AR-CGD exist. Clinical profile and mortality rates are similar in both X-linked and AR-CGD. However, this may be a reflection of the fact that milder forms of AR-CGD are probably being missed.